2022
DOI: 10.3390/ijms231911189
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Prevents Arterial Stiffness and Attenuates Hyperexcitation of Sympathetic Nerves in Perivascular Adipose Tissue of Mice after Transverse Aortic Constriction

Abstract: We aimed to investigate the efficacy of exercise on preventing arterial stiffness and the potential role of sympathetic nerves within perivascular adipose tissue (PVAT) in pressure-overload-induced heart failure (HF) mice. Eight-week-old male mice were subjected to sham operation (SHAM), transverse aortic constriction-sedentary (TAC-SE), and transverse aortic constriction-exercise (TAC-EX) groups. Six weeks of aerobic exercise training was performed using a treadmill. Arterial stiffness was determined by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…M2 macrophages have been reported to stimulate local sympathetic activation and growth in iWAT by releasing Slit3 [ 16 ], and our results showed that HIIT significantly increased Slit3 gene expression. Voluntary exercise reduces the expression of sympathetic markers in mesenteric adipose tissue of rats with polycystic ovary syndrome [ 34 ], and aerobic exercise attenuates hyperexcitation of sympathetic nerves in perivascular adipose tissue of mice after transverse aortic constriction [ 35 ]. However, the effects of exercise on local sympathetic nerves in subcutaneous adipose tissue are unclear and less reported.…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages have been reported to stimulate local sympathetic activation and growth in iWAT by releasing Slit3 [ 16 ], and our results showed that HIIT significantly increased Slit3 gene expression. Voluntary exercise reduces the expression of sympathetic markers in mesenteric adipose tissue of rats with polycystic ovary syndrome [ 34 ], and aerobic exercise attenuates hyperexcitation of sympathetic nerves in perivascular adipose tissue of mice after transverse aortic constriction [ 35 ]. However, the effects of exercise on local sympathetic nerves in subcutaneous adipose tissue are unclear and less reported.…”
Section: Discussionmentioning
confidence: 99%
“…An 8-week aerobic training also upregulated eNOS expression and NO level, while downregulated thrombospondin 1 and TNFα expressions in thoracic PVAT of obese rats [ 100 ]. Recently, chronic aerobic exercise was shown to raise PVAT adiponectin level in an induced mouse model of heart failure [ 101 ], suggesting that exercise can improve the paracrine function of PVAT. Moreover, continuous and interval running exercise could limit PVAT-secreted advanced glycation end products (AGEs) in swine [ 46 ], where accumulated AGEs in the vasculature perturb cell surface of ECs to cause oxidative and inflammatory insults [ 15 ].…”
Section: Physiological Means To Alter Pvat Functionmentioning
confidence: 99%